2021
DOI: 10.3390/nu13072222
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Micronutrients in Ageing Asia: What Can Be Implemented with the Existing Insights

Abstract: Life expectancy as a measure of population health does not reflect years of healthy life. The average life expectancy in the Asia-Pacific region has more than doubled since 1900 and is now above 70 years. In the Asia-Pacific region, the proportion of aged people in the population is expected to double between 2017 and 2050. Increased life expectancy leads to an increase in non-communicable diseases, which consequently affects quality of life. Suboptimal nutritional status is a contributing factor to the preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 134 publications
(146 reference statements)
0
8
0
Order By: Relevance
“…Multiple works of literature have shown that the FI is associated with several chronic physical health conditions [ 17 – 19 ]. Studies found that the lack of inadequate food leads to development of various chronic health condition such as hypertension [ 20 ], cardiovascular diseases [ 21 – 23 ], and diabetes [ 21 ]. Other than physical health, food insecurity has been known to impact cognitive function and mental health [ 11 , 12 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple works of literature have shown that the FI is associated with several chronic physical health conditions [ 17 – 19 ]. Studies found that the lack of inadequate food leads to development of various chronic health condition such as hypertension [ 20 ], cardiovascular diseases [ 21 – 23 ], and diabetes [ 21 ]. Other than physical health, food insecurity has been known to impact cognitive function and mental health [ 11 , 12 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inadequate nutrition caused by FI has also shown an association with unfavourable health outcomes such as obesity, anxiety, depression, and suicide, which activates the hypothalamic-pituitary-adrenal axis and triggers the secretion of glucocorticoids in the adrenal glands [ 24 , 25 ]. The deficiency of several vitamins and micronutrients also leads to various cognitive impairment which often leads to chronic health state, like Alzheimer’s [ 23 , 26 – 28 ]. So it is important to study the relevance of food insecurity in context of elderly which leads to cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%
“…Ageing is also associated with increased risk of NCDs 12 ; this could be a ramification of unavoidable physiological changes and could be accelerated by unhealthy diet, physical inactivity and sedentary life ( Figure ). Suboptimal nutritional status, particularly deficiency of micronutrients, is a contributing factor to the prevalence and severity of NCDs such as cardiovascular diseases (CVD), cognitive, musculoskeletal, metabolic and ophthalmic diseases 13 ( Table I ) 14 28 .…”
Section: Ageing and Nutritionmentioning
confidence: 99%
“…With rapidly ageing population in the world and the progress in medical care, more elderly patients are undergoing surgery 1 . Perioperative fluid management, one of the key components of enhanced recovery pathways, has been widely used in surgical procedures.…”
Section: Introductionmentioning
confidence: 99%